Uncommon cause (fecolith or enterolith) of small intestinal obstruction in the adult - Chowdhury, G; Kumar, AS; Rahman, A; Das, BC (Pulse, 2010)
Intestinal obstruction due to fecolith is a rare cause of small bowel obstruction. A 40 years old lady presented with the features of intestinal obstruction of 6 days duration. She had H/O laparatomy for DU perforation and hysterectomy. Clinical examination and investigations pointed to intestinal obstruction because of intestinal adhesions from previous surgeries. Conservative treatment did not give relief to the patient. Diagnostic laparoscopy revealed ascites and moderate adhesion A lump with hard consistency was detected in the terminal ileum. A diagnosis of lymphoma was made and hemicolectomy was planned. After mobilizing the caecum and part of ascending colon laparoscopically, small transverse incision was made in RIF. Whole mass and caecum was delivered through the wound. The mass in the ileum was felt moving proximally on traction. The mass was pushed proximally and enterotomy was made to take out the lump. It was a 6 x 4 x 2 cm fecolith (fig-3). There was no other abnormality or cause of intestinal obstruction except mild adhesion at the terminal ileum. DOI: 10.3329/pulse.v3i1.6555 Pulse Vol.3(1) July 2009 p35-37